If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(4x + 12) = 112 Reorder the terms: x(12 + 4x) = 112 (12 * x + 4x * x) = 112 (12x + 4x2) = 112 Solving 12x + 4x2 = 112 Solving for variable 'x'. Reorder the terms: -112 + 12x + 4x2 = 112 + -112 Combine like terms: 112 + -112 = 0 -112 + 12x + 4x2 = 0 Factor out the Greatest Common Factor (GCF), '4'. 4(-28 + 3x + x2) = 0 Factor a trinomial. 4((-7 + -1x)(4 + -1x)) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-7 + -1x)' equal to zero and attempt to solve: Simplifying -7 + -1x = 0 Solving -7 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -1x = 0 + 7 -1x = 0 + 7 Combine like terms: 0 + 7 = 7 -1x = 7 Divide each side by '-1'. x = -7 Simplifying x = -7Subproblem 2
Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4Solution
x = {-7, 4}
| 1-4v=-6+3v | | 32=16v | | 32=16 | | 81y^2-4=0 | | 6x-3+5=6x+1 | | -4(d+5)-3d8= | | 5+6n=-7+4n | | 7=2x+17 | | 4n^2-7n=2 | | -n+3n=6n+16 | | 3-2*-7=17 | | -2(y-3)=12 | | 2a^2+8a=-30 | | 12s^3t^3+3s^4t^2= | | 4=5x-24 | | x^2-5x-32=0 | | x=-2y-15 | | In(2x+1)-1=In(x-2) | | 2x^3+3x^2+36x=0 | | -(-2b^2+3)-b(2b-3)-3= | | 35(p-3)=-4 | | -14=10+3x | | -5x+4x+5=48 | | 4y+7=8y-5 | | -32-(-9)= | | 25s^3t^4+5s^4t^3= | | 2d^4=5d | | -9+6x=5x+12 | | (2x-13)+(x+41)+(x)=180 | | 5(5x-2)=-6(x+2) | | 9x=10x+90 | | -56+x=32+5x |